The Virginia Speedways Project:: Researching the Landscape of the Virginia Speedways - KATEN, Brian (ARCC Conference Repository, 2019)
In the late 1940’s rural Virginia and North Carolina saw the rise of a regional sport - stock car racing - that would come to epitomize for many people an image of the rural south of the mid to late twentieth century. The evolution of stock car racing was accompanied by the development of a significant social and physical Virginia landscape that thus far has been neglected in contemporary scholarship: the short track. Carved from farmer’s fields and natural amphitheaters new tracks, or "speedways" first appeared as temporary landscapes associated with the weekly ritual of racing competition. But by the 1950’s full time tracks and their featured event, "Saturday Night Racing", were significant features in the social and recreational landscape of small towns throughout Virginia. Deeply rooted in their communities, today those tracks that remain are important landscapes of community pride, social intercourse, ritual, and entertainment. Viewed collectively the Short Tracks offer a unique opportunity to add to our understanding of the Virginia landscape as a rich and varied series of layers to be experienced. More importantly the short tracks can be clearly presented and understood as a significant contemporary layer to the Virginia landscape. As such, they can augment the more commonly recognized layers of the Virginia landscape: the James River plantations, the state’s civil war battlefields, the Virginia county courthouse complexes, and the Virginia mineral springs. Despite their significance within their communities and the larger Virginia landscape, the short tracks are at risk. Changing economics and expanding development have led to the closing of many of the early tracks, but a significant number of tracks have survived. These tracks comprise a significant cultural landscape that deserves to be recognized as a landscape of historical importance and contemporary economic potential. This paper will present on-going research on the lost vernacular landscape of the Virginia short track circuit of the 1940’s 50’s and 60’s. Through interviews with former drivers and track officials over 60 lost community tracks have been thus far been identified in addition to the twenty-four tracks still in operation. Mapping of the lost tracks is underway and their landscapes are being reconstructed through period images and maps, written descriptions, and interviews with participants, track officials, and sponsors. This paper will also demonstrate the important role of GIS in mapping and understanding those landscape layers associated with the tracks and GIS’s expanding role in understanding historic landscapes. The lost and existing tracks will be revealed as landscapes of community pride, social intercourse, ritual, and entertainment of interest to landscape historians, historical landscape architects, preservationists, and contemporary designers.